DURING WORLD WAR II TRAINING OF MILITARY PERSONNEL (On the example of the Chirchik High Tank Command Engineering Academy) (American Journal of Research in Humanities and Social Sciences, 2023)
It is well-known that our people's contribution to the Great Victory has not yet been fully studied, but in the years that followed, a huge amount of work began to be done in this direction. In particular, it was possible to study previously confidential archive documents, materials not known to the scientific community. Cooperation with archive organizations, museums and funds, historians and experts, and the Governing Body has been strengthened in this regard. Scientific research has published very important new information about the participation of our people in World War II and our heroic ancestors. They are currently widely media, in books and albums.